Response to hepatitis B vaccine in patients with non-hepatitis B chronic liver disease - Faruk AĞAN; Yılmaz ÇOLAKOĞLU; Atilla ÖKTEN; Selim BADUR; Levent ERDEM; Selim GÜREL; M. Derya ONUK; Fatih BEŞIŞIK; Sabahattin KAYMAKOĞLU (Turkish Journal of Gastroenterology, 2019)
-